Efficacy of repeated low-dose bevacizumab treatment with long-dosing interval for radiation-induced brain necrosis: A case report. Issue 1 (2nd January 2017) - Meng, Xiangying; Zhao, Rugang; Wu, Shikai; Shen, Ge; Ding, Lijuan; Sun, Bing; Wang, Junliang
ABSTRACT: A 40-year-old Chinese female patient, with radiation-induced brain necrosis after radiosurgery, was treated 6 times with a single dose of 200 mg (3.27 mg/kg) bevacizumab each time, and with an interval of 12–16 weeks between each treatment. Neurological symptoms such as dizziness, fatigue, and headache disappeared after each administration of bevacizumab. The results suggest that repeated bevacizumab treatment using a low-dose and long-dosing interval may significantly alleviate radiation necrosis and its symptoms.